Implementation of a Violence Risk Assessment and Interventions Aimed at the Prevention of Patient-Perpetrated Violent Events Across Care Settings. (March 2023) - Croland, Jennifer; Overton, Sarah; Nimtz-Rusch, Kelly; Emmerling, Sheryl; Wiegand, Lori
Abstract : Healthcare worker violence at the hands of patients is the leading cause of workplace injury with reports demonstrating yearly increases. Literature suggests organizational strategies to reduce workplace injury are necessary to create safe environments for patients to receive care and for healthcare workers to practice, but tactics lack a care continuum focus and largely focus on deescalation and management of violent events. One healthcare system identified that the use of an assessment widely used in Canada, identifying patients at risk for violent behaviors, would supplement already existing efforts at protecting patients. The implementation of this tool across care settings is presented in this article.